2011
DOI: 10.1074/jbc.m110.186510
|View full text |Cite
|
Sign up to set email alerts
|

Arrangement and Mobility of the Voltage Sensor Domain in Prokaryotic Voltage-gated Sodium Channels

Abstract: Prokaryotic voltage-gated sodium channels (Na V s) form homotetramers with each subunit contributing six transmembrane ␣-helices (S1-S6). Helices S5 and S6 form the ion-conducting pore, and helices S1-S4 function as the voltage sensor with helix S4 thought to be the essential element for voltage-dependent activation. Although the crystal structures have provided insight into voltage-gated K channels (K V s), revealing a characteristic domain arrangement in which the voltage sensor domain of one subunit is clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…The sp-pore was tetrameric in the absence of the voltage sensor subdomain, which suggests that the association between monomers in the channel is largely mediated at the interfaces between the S5 and S6 transmembrane segments. Isolated voltage sensor domains do not assemble as tetramers (17, 18). It is therefore likely that the pore region (including its C terminus) is pivotal for forming the tetramers in the intact channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sp-pore was tetrameric in the absence of the voltage sensor subdomain, which suggests that the association between monomers in the channel is largely mediated at the interfaces between the S5 and S6 transmembrane segments. Isolated voltage sensor domains do not assemble as tetramers (17, 18). It is therefore likely that the pore region (including its C terminus) is pivotal for forming the tetramers in the intact channels.…”
Section: Discussionmentioning
confidence: 99%
“…The pore subdomains form a compact central transmembrane pathway capable of accommodating ions in both selectivity and cavity regions; this is surrounded by the relatively loosely associated voltage sensor subdomains. Isolation and expression of the N-terminal four-transmembrane voltage sensor subdomain of the NaChBac channel (17) showed that the voltage sensor alone was capable of folding in the absence of the pore subdomain, and EPR measurements confirmed that it has a more tightly packed but similar overall fold to that of potassium voltage sensors (18). Here we designed a pore-only version of the Na v sp bacterial sodium channel and investigated whether it formed folded, stable tetramers and was capable of supporting Na + -specific ion channel permeability in the absence of the voltage sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining the membrane potential at a more negative voltage than À180 mV for a long time, however, was very difficult. E43K and D60K of NaChBac, a BacNav homologue of Bacillus halodurans, are well known mutations that positively shift the voltage dependence of the activation [33]. In this protocol, run-down of the current of NavAb WT was not observed (Fig.…”
Section: Crystal Structure Of the Navab Wt In The High-ph Conditionmentioning
confidence: 90%
“…High resolution images of radiation sensitive organic molecule, such as silver-7, 7 0 , 8,8 0 -tetracyanoquinondimethan complex, Ag-TCNQ, were easily and reproducibly observed by the MDS. 16 Unlike organic molecules, biological molecules are extremely radiation sensitive, and the resolution of their images is therefore strongly restricted by radiation damage.…”
Section: High Resolution Electron Microscopymentioning
confidence: 96%
“…6 Although no three-dimensional (3D-) structure has been determined yet for bacterial Na þ channels, mobility of voltage-sensor domains has been observed mainly by electrophysiology. 7,8 Simultaneously, we are studying water channels, which should be important for brain functions, because water content in brain is, remarkably, up to 85% and ion permeation has to be blocked to ensure the ion channel function, even when water molecules rapidly pass through the channels. A predominant water channel in brain is aquaporin-4 (AQP4).…”
Section: Introductionmentioning
confidence: 99%